Maternal morbidity in emergency lower segment cesarean section - Kalpana, P.; Praveena, T. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: With a steep fall in maternal mortality and morbidity and with much more liberalization of indications, the incidence of cesarean section rate has greatly increased over the last thirty years and almost doubled in the current decade. The objective of this study was to study incidence of maternal morbidity in emergency lower segment cesarean section. Methods: Hospital based prospective study was carried out among 200 women undergoing emergency lower segment cesarean section. Data relating to demographic characteristics, clinical characteristics, maternal and fetal indications, incidence of morbidity, and types of morbidities, Intra operative complications, and Post operative complications was noted down. Chi square and odds ratio was used for statistical analysis. Results: The incidence of LSCS was 24.21%. Incidence of emergency LSCS was 96.74%. 71% were having primary LSCS and 20.5% were booked cases. The most common maternal indication for emergency LSCS was pregnancy induced hypertension and eclampsia in 32.5% of the cases. The most common fetal indication for emergency LSCS was fetal distress in 60%. Incidence of morbidity was 35% and it was associated with booking status, parity and social class. Incidence of intraoperative complications was 23.5%. Majority (18.5%) developed febrile morbidity followed by wound sepsis in 12.5%, urinary tract infection in 8%, mastitis in 7.5%, respiratory tract infection in 7%, wound gaping in 4%, paralytic ileus in 3%, endometritis in 2.5%, postpartum hemorrhage in 1.5%, 2 cases of burst abdomen and one case of small bowel obstruction. Conclusions: Emergency LSCS was more common than elective LSCS and it was associated with booking status, parity and social class.